SUSTAINABILITY SYSTEM TO BENEFIT BOTH GUEST AND HOTELS ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: The research paper was to develop a universal sustainability rewards program in an upscale business  hotel. With growing concern for depleting natural resources this program aims at rewarding guests for conserving  natural resources. Objective: The study was to identify the consumer behavior and perception towards sustainability  and to curate a universal sustainable rewards program. This study proposes a conceptual framework that combines  the principles of sustainability, customer loyalty, and corporate social responsibility to design a rewards program that  promotes environmentally responsible behaviors among hotel guests. Methodology: Quantitative research design was  used in which an energy survey of a two hotels was conducted through telephonic interview with the Incharge of the  Hotel Engineering Department and a survey among five hundred general consumers was done to assess their attitudes  and behaviors towards sustainability through a Google form. The data was analyzed by calculating frequency and  percentage. Results: The findings indicated that sustainable practices have become increasingly important to guests  (92%) and 98% feel that an encouraging program would be an effective way to promote sustainable behaviors. The  study also identified the key features and benefits of a sustainability programs and around 90% of customers prioritize  sustainability efforts and innovations when selecting their accommodations, reinforcing the on-going trend observed in  consumer behaviour. Around 81.3% of respondents expressed their willingness to partake in a universal sustainability  rewards program and provided recommendations for its successful implementation in hotels. The rewards program  gives credit points for optimal conservation of resources. It is universal in nature, i.e. these points can be earned as  well as utilized anywhere across the globe. Conclusion: The proposed program has the potential to enhance the hotel’s  reputation as a socially responsible business, attract environmentally conscious guests, and contribute to the sustainable  development of the hospitality industry.
Keywords: Sustainability; Hospitallity Industry; Hotels; Guests; Environment